Developing an AI and Generative AI Literacy Framework: A Lesson from an Islamic Higher Education Institution - Rohadi, Tedi; Utami, Dini (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This study addresses this gap by developing and validating an AI and GAI literacy framework that aligns with the mission of Islamic higher education. Using a Research and Development (R&D) design guided by the ADDIE model, the study involved 25 fifth-semester students and 3 lecturers from the English Language Teaching Department at UIN Sunan Gunung Djati Bandung. Data were collected through questionnaires, semi-structured interviews, focus group discussions, classroom observations, and expert validation checklists. Quantitative analysis showed that students scored highest in ethical understanding (M = 4.0, SD = 0.55) but lowest in critical awareness (M = 2.8, SD = 0.70), while lecturers outperformed students across all dimensions, particularly in ethical understanding (M = 4.3, SD = 0.50) and pedagogical integration (M = 3.8, SD = 0.57). Qualitative findings revealed that students primarily used AI tools for basic academic tasks, whereas lecturers applied them in broader pedagogical contexts, with both groups emphasizing ethical responsibility. Expert validation confirmed the framework’s high validity (overall mean = 4.5/5), particularly in ethical-Islamic alignment. These findings suggest that AI and GAI literacy in Islamic higher education must extend beyond technical proficiency to include critical reflection and ethical integration, ensuring that the use of AI is both pedagogically meaningful and culturally contextualized. The resulting framework contributes to local practice while also enriching global discussions on culturally embedded approaches to AI literacy in higher education.